Pengaruh Penggunaan Media Flashcard Dalam Pembelajaran Seni Rupa Terhadap Hasil Belajar Siswa Kelas III - Najla Hana Mawaddah Tanjung; Sri Mustika Aulia; Wildansyah Lubis; Husna Parluhutan Tambunan; Try Wahyu Purnomo (Jurnal Keluarga Sehat Sejahtera, 2026)
This study is underpinned by the low learning achievements of students in the Fine Arts subject at Grade III of UPTD SDN 016523 Teladan, attributed to the application of conventional teaching methods and the limited use of engaging visual aids, which consequently led to diminished student motivation and involvement. The primary objective of this research is to examine the impact of utilizing flashcard media on enhancing students' academic performance. The adopted approach constitutes a quantitative study employing a quasi-experimental design based on the Two Group Pretest–Posttest Model, with Grade III students serving as the primary subjects. The research implementation encompassed preparation phases, intervention delivery via flashcard media, and assessment through pre-intervention and post-intervention tests. The analysis results reveal a significant improvement in students' learning achievements following the intervention, as evidenced by the differences in pretest and posttest scores. These findings affirm the efficacy of flashcard media in strengthening mastery of lesson concepts and boosting student participation in Fine Arts instruction. Accordingly, flashcard media can be recommended as an effective teaching innovation to support the enhancement of instructional quality and learning outcomes at the elementary school level.